Family, Power and Religiosity of an Aristocratic Woman in Galicia during Late Middle Ages. The Last Wills of dona Xoana de Castro (1467) - García-Fernández, Miguel (Madrygal. Revista de Estudios Gallegos, 2018)
Dona Xoana de Castro was an outstanding noblewomen who lived in Galicia during the 15th Century, linked to two of the main lineages at that time: the House of Castro –because their original family was the Castro de Castroverde family– and the House of Moscoso –because she was married with Rodrigo de Moscoso, becoming, in addition, the mother of the successors of the lineage. Although there are several scattered data about this noble, until now we did not know her last wills. Therefore, the aim of this paper is to publish her last wills and testament, preserved in a copy of Early Modern Age, and, at the same time, offer a brief historical approach to the family, power and religiosity of Dona Xoana. In this way, it will be possible to analyze her last wills in their context and, at the same time, to approach the life and actions of this aristocrat woman who had a remarkable social and economic role, especially during her widowhood, evidencing, once again, that noblewomen were not mere “ladies locked in castles”.